The Design of a Web-Based Program for Reporting Incomes Tax Article 21 for Civil Servants - Damayanti Damayanti; Tri Sandhika Jaya (STIE Malangkucecwara, 2018)
This research aimed to created a model program of tax retun (SPT) of income tax article 21 especially for civil servants. The method of data collection used in this researchr are field research through the face-to-face interview and observation in district TBS, Inspectorate of Bandar Lampung and Politeknik Negeri Lampung. The result from this research is the formation of modelling of program SPT income tax article 21 special for civil servants which withholding tax slip both final and non final can be printed online. This program is made to resolved the problem especially for civil servants who only received the withholding tax slip from their regular income. A withholding tax slip that can be printed later is a form 1721 A2 (non final) which is obtained once a year, while a form 1721-VII (final) will be obtained whenever employee received their income.